Bypassing use-dependent plasticity in the primary motor cortex to preserve adaptive behavior - M. Bosc (Nature Portfolio, 2021)
Abstract Behavioral adaptation, a central feature of voluntary movement, is known to rely on top-down cognitive control. For example, the conflict-adaptation effect on tasks such as the Stroop task leads to better performance (e.g. shorter reaction time) for incongruent trials following an already incongruent one. The role of higher-order cortices in such between-trial adjustments is well documented, however, a specific involvement of the primary motor cortex (M1) has seldom been questioned. Here we studied changes in corticospinal excitability associated with the conflict-adaptation process. For this, we used single-pulse transcranial-magnetic stimulation (TMS) applied between two consecutive trials in an interference flanker task, while measuring motor-evoked potentials (MEPs) after agonistic and antagonistic voluntary movements. In agonist movement, MEP amplitude was modulated by recent movement history with an increase favoring movement repetition, but no significant change in MEP size was observed whether a previous trial was incongruent or congruent. Critically, for an antagonist movement, the relative size of MEPs following incongruent trials correlated positively with the strength of behavioral adaptation measured as the degree of RT shortening across subjects. This post-conflict increase in corticospinal excitability related to antagonist muscle recruitment could compensate for a potential deleterious bias due to recent movement history that favors the last executed action. Namely, it prepares the motor system to rapidly adapt to a changing and unpredictable context by equalizing the preparation for all possible motor responses.